Diseño y planificación del instituto superior tecnológico de artes Daniel Reyes en la parroquia San Antonio de Ibarra - Espinoza Herrera, Edwin Santiago (2024)
The Higher Technological Institute of Art Daniel Reyes has been a solid institution and recognized for its formation of artists at national and international level. However, over the years, a decrease in the artistic tradition has been observed due to the lack of adequate infrastructure for future high school graduates interested in studying at this institution. To address this problem, the design and planning of the Higher Technological Institute of Art Daniel Reyes in the San Antonio de Ibarra is proposed. The objective is to provide future generations with a quality option in terms of infrastructure and artistic education. Semi-structured surveys were conducted with current students of the Higher Technological Institute of Art Daniel Reyes. These surveys revealed that students lose interest in studying arts-based careers due to the lack of adequate facilities and an inauspicious environment. The proposed architectural project aims to promote the institute as the central axis of the San Antonio de Ibarra Parish. In addition, it seeks to contribute to the social sphere by providing an adequate space for artistic training. This project seeks to revitalize the artistic tradition and offer a quality option for students interested in the arts in the region. The Higher Technological Institute of Art Daniel Reyes will continue to be a reference in artistic education and will contribute to the cultural development of the community.